The Agribusiness Innovation Center of Tanzania : Scaling Value-Adding, Post-Harvest Processing Agribusinesses - Brethenoux, Julia; Charles, Kathleen; Giddings, Steven; Okello, Julius; Olafsen, Ellen; Temu, Andrew (World Bank, Washington, DC, 2014)
Tanzania has tremendous potential to support a thriving agribusiness sector. Agriculture is diverse and extensive, employing more than 80 percent of the population, and contributing about 28 percent of Gross Domestic Product, or GDP and 30 percent of export earnings. A wide range of agricultural commodities are produced in Tanzania, including fiber (sisal, cotton), beverages (coffee, tea), sugar, grains (a diverse range of cereals and legumes), horticulture (temperate and tropical fruits, vegetables and flowers) and edible oils. This document proposes a new model for promoting the growth of competitive value-added sunflower oil processing in Tanzania, and also seeks to identify potential growth enterprises in other value chains. The Agribusiness Innovation Center (AIC) will provide a set of financial and non-financial services to high-growth potential entrepreneurs, aiming to accelerate the growth of their enterprises and demonstrating product, process, and business model innovation across focal sectors. The AIC will complement existing efforts focused on farm-level improvements and foreign investment facilitation.